Wetland landscape characterization : practical tools, methods, and approaches for landscape ecology - Lopez, Ricardo D.; Lyon, John G.; Lyon, Lynn Krise; Lopez, Debra K. (CRC Press, 2013)
This book explains how to locate, identify, and map the extent of wetlands to learn more about their importance to society and the larger landscape. It examines jurisdictional, regulatory, and practical applications from the scientific, engineering, and lay perspectives. The book reflects an emerging infrastructural, ecosystem goods-and-services perspective to better assist readers who may encounter these concepts and challenges as they assess and characterize wetlands. Examples and case studies illustrate a variety of situations and solutions, highlighting the use of current techniques to assess, inventory, and monitor natural resources under changing conditions.--